Comparative proteomic analysis of a Candida albicans DSE1 mutant under filamentous and non‐filamentous conditions. Issue 11 (14th October 2014) - Zohbi, Rasha; Wex, Brigitte; Khalaf, Roy A.
Abstract Candida albicans is a common opportunistic pathogen that causes a variety of diseases in immunocompromised hosts. In a pathogen, cell wall proteins are important virulence factors. We previously characterized Dse1 as a cell wall protein necessary for virulence and resistance to cell surface‐disrupting agents, such as Calcofluor white, chitin deposition, proper adhesion and biofilm formation. In the absence of decomplexation, our objectives were to investigate differential proteomic expression of a DSE1 mutant strain compared to the wild‐type strain. The strains were grown under filamentous and non‐filamentous conditions. The extracted cell proteome was subjected to tryptic digest, followed by generation of peptide profiles using MALDI–TOF MS. Generated peptide profiles were analysed and unique peaks for each strain and growth condition mined against a Candida database, allowing protein identification. The DSE1 mutant was shown to lack the chitin biosynthesis protein Chs5, explaining the previously observed decrease in chitin biosynthesis. The wild‐type strain expressed Pra1, involved in pH response and zinc acquisition, Atg15, a lipase involved in virulence, and Sod1, required for oxidative stress tolerance, in addition to proteins involved in protein biosynthesis, explaining the increase in total protein content observed compared to the mutants strain. The mutant, on the other hand, expressed glucoamylase 1, a cell wall glycoprotein involved in carbohydrate metabolism cell wall degradation and biofilm formation. As such, MALDI–TOF MS is a reliable technique in identifying mutant‐specific protein expression in C. albicans. Copyright © 2014 John Wiley & Sons, Ltd.